(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
Classification of silo grain storages by location in space were fulfilled; advantages and disadvantages of different types of horizontal and vertical silo grain storages were analyzed; constructive elements of round steel flat bottom silo and hoppered bottom silo were examined. Keywords:horizontal silo, vertical silo, roof, hoppered bottom silo, flat bottom silo.